Attitudes of sports activity supervisors towards the participation of students with disabilities in school sports activities in West Bank schools - Jamhour, Haifa Abdullah (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the attitudes of school sports activity supervisors in West Bank schools toward the participation of the disabled in school sports activities, the study sample targeted all the supervisors of the school sports activity, which numbered (39) supervisors. For Social Sciences-SPSS V.23) the The results of the study conducted in the summer of 2022 showed that the attitudes of the sports activity supervisors towards the participation of people with disabilities in school sports activities in the schools of the West Bank are neutral, the study also showed that there are no statistically significant differences in the attitudes of the sports activity supervisors in the schools of the West Bank due to the Gender Variable, as well as the absence of statistically significant differences in the attitudes of sports activity supervisors due to the school dependency variable (governmental, private). The researcher recommended: Paying attention to raising awareness of the importance of the participation of people with disabilities in sports activities for the disabled themselves, as well as conducting studies on the attitudes of people with disabilities towards participating in school sports activities.